STRATEGI PENGEMBANGAN PAGUYUBAN KELUARGA DAN PEDAGANG TANAMAN HIAS, SEBAGAI “ LEMBAGA KOPERASI PRIMER “ KAMPUNG WISATA BUNGA, DI DESA BANYUURIP, KEC. KEDAMEAN, KAB. GRESIK - Sri Andayani; Sumiati Sumiati (Media Mahardhika, 2022)
Situation analysis Gresik Regency is one of the regencies in East Java, which used to be very well known as an industrial city because there are many industrial companies, one of which is "Semen Gresik" but here are also quite a lot of tourist sites which are also frequented by local tourists, as well as local tourists. from foreign countries, in the southern region of Gresik Regency, precisely located in Miru Hamlet and Pendem Hamlet which is in Banyuurip Village, Kedamean District, has the largest ornamental plants, has the potential for an export market that is wide open. The location of this village is very strategic, being a center for ornamental plants with various types of plants including: Antorium, Chrysanthemum Orchids, Ferns, Cacti, Bonsai, and others. In the village of Banyuurip, there is a flower farmer association with around 914 members. This ornamental plant business association has not yet been in the form of an institution such as a Cooperative. With the above problems, the research team from Untag Surabaya intends to conduct a research entitled: Development Strategy for the Association of Ornamental Plant Farmers and Traders, as a Primary Cooperative Institution, "Kampung Wisata Bunga" in the village. Banyuurip, Kec. Kedamean, Gresik Regency. Research problem: How is the Strategy for Development of the Association of Farmers' Families and Ornamental Plant Traders, as the Primary Cooperative Institution, "Kampung Wisata Bunga" in Banyuurip Village, Kec. Kedamean, Gresik Regency? Research objectives: 1.Mapping the legal entity form of the Association of Farmers' Families and Ornamental Plant Traders, which already exist in Banyuurip Village. 2. Improving the form of the Association of Farmers' Families and Ornamental Plant Traders, towards a Cooperative Legal Entity to support the activity of "Flower Tourism Village, in Kab. Gresik. Research outputs a. Research reports that can be used as input for the Gresik Regency Government in making policies for the Association of Farmer Families and Ornamental plant traders in developing the "Flower Tourism Village" destination in Banyu Urip Village, Kab. Gresik. b. Scientific Journals with ISSN or Indexed Journals and Plans for Cooperative Legal Entities Research Methods; SWOT analysis. The results of the study: The IFAS matrix area is 0.66 and the EFAS is 0.71. Matrix breadth and strategy priorities 1. Aggressive, 2 Diversification, 3 Defensive, 4. Turnaround.